Level of knowledge, attitudes and substance use among students of primary and secondary schools in Belgrade 2010/2011: Pilot study - Dimitrijević Ivan,; Brković Danijela; Dimčić-Tasić Gorica; Anđelić Spaso; Damnjanović Dragi; Nikolić Draga; Blagojević Slavka; Bauman Stefan; Janković Slaviša (Sanamed, 2011)
In order to organize prevention of substance abuse in the community, it is necessary to provide research on the level of knowledge, attitudes and patterns of use of particular substances within youth. In Belgrade, the Commission for the prevention of substance abuse among youth has done the research during the 2010/2011. The representative sample consisted of 1103 students from 16 primary and secondary schools in the city of Belgrade. We applied a specially designed questionnaire on the level of knowledge for particular classes of substances as well as new forms of addiction (internet, gambling). Important are data on different levels of students' knowledge about certain classes of substances. The low level of correct answers was noted for the way of cannabis use (5.3%), the consequences of amphetamines use (0.8%), the effects of opiates (1.9%), ways of using opiates (1.4%), effects of steroids (0.7%), the types of inhalants (3.8%), types of synthetic drugs (18.7%) and the ability to detect substances in the urine (0.5%). The high level of correct answers was noted on the issue of the consequences of using marijuana (84.4%), sedatives (89.4%), possibility the Internet addiction (85.7%), computer games dependence (86.4%) and betting (90.9%). This work provide guidelines for educational programs in order to improve students' knowledge in this field.